JURIDICAL ANALYSIS OF STATE FINANCIAL POLICIES IN HANDLING THE COVID-19 PANDEMIC - Wirawan, Arka; Samadi, Wibowo Murti; Kusumastuti, Dora (Sekolah Tinggi Ilmu Hukum Awang Long, 2023)
The purpose of this research is: to juridically analyze state policies in handling the Covid-19 pandemic through Law Number 2 of 2020. The writing method used in this research is normative juridical using a statute approach and conceptual approach. Based on the results of the discussion and research, it can be concluded that based on the system of division of powers in Indonesia contained in the 1945 Constitution as the state constitution, the President is given the authority to establish regulations which hierarchically have the same degree as laws known as Government Regulations in Lieu of Laws (Perppu). The existence of Perppu is also widely regulated in countries that apply the presidential system. In addition, the stipulation of Perppu must be based on the existence of a compelling urgency that is temporary (emergency). The category of compelling urgency is the prerogative of the President. Furthermore, legislators can accept or reject the Perppu into law as a definitive rule of law or law. Testing Perppu is the authority of the legislature to accept or reject the Perppu.